Effect of acid treatment on the multiwalled carbon nanotubes - Rahmam, S. (Maney Publishing, 2014)
Carbon nanotubes (CNT) have gained great interest for research in many applications because of their unique characteristics, such as having high porosity, high surface area and the ability to be functionalised by a wide spectrum of surface functional groups. However, owing to the hydrophobic nature, CNT could not be dispersed uniformly in the solution, thus restricting the applications of CNT in industry. In order to resolve this problem, multiwalled carbon nanotubes (MWCNT) were treated with nitric acid (HNO3), and the mixture of HNO3 and sulphuric acid (H2SO4). Different reagents for acid treatment seem to affect the bundling arrangement of nanotubes, the attachment of functional groups and the degree of functionalisation. The treated MWCNT resulted in lesser agglomeration of nanotubes, reduced the impurities, and give more attachment of functional groups. The treated MWCNT samples that have more functional groups can be considered as a potential material for applications. Â© 2014 W. S. Maney & Son Ltd.